2020
DOI: 10.1177/1591019920946507
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of staged angioplasty for treating carotid stenosis with a high risk of hyperperfusion: A single-center retrospective study

Abstract: Objective Hyperperfusion syndrome (HPS) following carotid artery stenting (CAS) is a rare but life-threatening complication. Staged angioplasty (SAP) is an alternative method that prevents HPS by preventing a sudden increase in cerebral blood flow. In this study, we investigated the safety and efficacy of SAP. Methods A total of 114 patients with carotid stenosis underwent CAS treatment in our hospital between September 2014 and September 2019. Patients with severe stenosis and poor collateral circulation show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Ten studies were included in this meta-analysis. Among these, one article was randomized control trial 8 and nine articles were non-RCTs (four non-controlled studies 1417 and five case-control studies 4 , 6 , 911 ). The main characteristics of the included studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies were included in this meta-analysis. Among these, one article was randomized control trial 8 and nine articles were non-RCTs (four non-controlled studies 1417 and five case-control studies 4 , 6 , 911 ). The main characteristics of the included studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included all patients with symptomatic carotid stenosis (defined as carotid stenosis associated with stroke or transient ischaemic attack), 8 , 14 , 16 , 17 four studies included patients with asymptomatic or symptomatic carotid stenosis, 6 , 9 , 11 , 15 and two studies only included patients with carotid stenosis without reference to asymptomatic or symptomatic stenosis. 4 , 10 Eight studies reported on elective procedures only, 4 , 6 , 911 , 1517 two studies might recruit acute patients based on the description of their method. 8 , 14 The endpoint of efficacy and the endpoint of safety were evaluated in this meta-analysis as shown in Supplementary Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations